Dynamics of Islamic Politics in the Early Period of the New Order - Rahman, Abdul (Formosa Journal of Sustainable Research, 2024)
This article aims to review the relationship between proponents of Islamic politics and the New Order government. This article uses historical methods, namely heuristics, criticism, interpretation, and historiography. The research results show that the emergence of the New Order government cannot be separated from the support of military groups and Islamic political forces. The Islamic group's support for the New Order government was related to this group's desire to be involved in implementing state policies, especially in the field of government politics. This desire turned out not to be as expected, because the struggle of Islamic groups in political channels received restrictions and pressure from the government because it was considered to threaten national integration and development